Protection against malaria is conferred by passive transferring rabbit F(ab)2' antibody fragments, induced by Plasmodium falciparum MSP-1 site-directed designed pseudopeptide-BSA conjugates assessed in a rodent model (2011)
F(ab)2'-immunoglobulin (Ig) fragments induced by site-directed designed immunogens are emerging as novel tools of potential utility in the treatment of clinical episodes of transmissible diseases such as malaria. Immunogens based on reduced amide pseudopeptides based on site-directed molecular modifications represent structural probes that could be considered as novel vaccine candidates, as we have previously demonstrated. We have obtained F(ab)2'-Ig rabbit antibodies induced against the N-terminal sequence of the native Merozoite Surface Protein-1 (MSP-1) of Plasmodium falciparum and a set of five MSP-1-derived reduced amide pseudopeptides. Pseudopeptides were designed for inducing functional neutralizing mono-specific polyclonal antibodies with potential applications in the control of malaria. Following a classical enzyme immunoglobulin fractionation, F(ab)2'-Ig fragments were tested for their ability to suppress blood-stage parasitemia by passive immunization in malaria-infected mice. Some of these fragments proved totally effective in suppressing a lethal blood-stage challenge infection and others reduced malarial parasitemia. These data suggest that protection against Plasmodium yoelii malaria following passive transfer of structurally well-defined ?-strand F(ab)2'-Ig fragments can be associated with specific immunoglobulins induced by site-directed designed MSP-1 reduced amide pseudopeptides. © 2010 Elsevier Ltd.